Communication Experiences of Speech and Hearing Impaired Clients in Accessing Healthcare in Hohoe Municipality of Volta Region, Ghana - Prince Kubi Appiah; Georgina Agartha Fenu; Geoffrey Adebayo Asalu; Wilson Mensah Dzata; Duut Abdulai Bonchel; Timay Ibrahim Abdul-Rahman; Anthony Zunuo Dongdem (European Scientific Journal, ESJ, 2018)
Background Access to healthcare for speech and hearing impaired clients can be difficult against the backdrop that healthcare providers are inadequately trained to work with Deaf clients whose primary mode of communication is sign language. Therefore, this study sought to explore communication experiences of deaf people and barriers affecting their access to healthcare in Hohoe municipality in Volta region of Ghana. Method: For this quantitative and qualitative cross-sectional study 40 participants were recruited through snowball sampling technique. Quantitative data was obtained through administration of semi-structured questionnaire to sixteen (16) willing participants. The information was triangulated with three (3) focus group discussions. The statistical software Epi Info version 7 and Stata version 11 was used to analyze the quantitative data and presented in graph and tables. Thematic analysis was adopted for analyzing the qualitative data. Findings: Majority (93%) of the study participants are deaf and 7% being hard of hearing. Half (20) of them were above 30 years. Male to female participants in the study were equal. Thirty-five percent of participants had at least primary education and 10.0% had no formal education however 28% of them were employed. Gestures, sign language, assistance from a family member/friend, lip reading and writing are the various methods used by the deaf in communicating with healthcare providers. Family member/friends assistance and gestures were the most frequently used methods of communicating. Due to communication difficulties, they experience disparity, discriminations, neglect and delays in receiving healthcare from providers. Financial difficulties was also identified as barrier in accessing health. Conclusions: Access to healthcare for hearing impaired clients is important to achieve health equity. However challenging it can be, due to communication gaps, efforts must be made to ensure that this group receive adequate health care.